If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 10 = 2x + -35 Reorder the terms: 10 + 7x = 2x + -35 Reorder the terms: 10 + 7x = -35 + 2x Solving 10 + 7x = -35 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + 7x + -2x = -35 + 2x + -2x Combine like terms: 7x + -2x = 5x 10 + 5x = -35 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + 5x = -35 + 0 10 + 5x = -35 Add '-10' to each side of the equation. 10 + -10 + 5x = -35 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = -35 + -10 5x = -35 + -10 Combine like terms: -35 + -10 = -45 5x = -45 Divide each side by '5'. x = -9 Simplifying x = -9
| 7x-9+80=13x+17 | | 23+36+x=67 | | 26x-52y=104 | | 5(-2)-5(4)-3(4x)+3(5)=97 | | 14X+9=3X+30 | | 4w-18=34 | | 0.4-2.5=1.3+4.7 | | g+575=4293 | | -19x-10=-9x+20 | | a(x-5)=9x-25-2x-10 | | -17=-2n+7 | | -3b+2b=8 | | 5.5+6=12 | | 5(-2-4)-3(4x+5)=97 | | 7.5-2*x=4.3 | | 0.6x+0.2=-1.16 | | n+9=4n-3 | | 8n=2 | | x+7=5-2 | | 53+7=13x-1 | | 6638+c=6638 | | x/7-3=3/14 | | 8x=54-x | | 4709+j=5000 | | 10-3(m-2)=0 | | 3p-3=2p+7 | | 4p=12p-24 | | 4.3=7.5-2*x | | 1943+d=2422 | | X=0.587 | | 3.8b+1.5b=1.2-1.9b | | x+x+x+2=x-6 |